2015
DOI: 10.1163/15685314-04306008
|View full text |Cite
|
Sign up to set email alerts
|

Is Local Community the Answer?

Abstract: This article critically examines claims that “local community” and “local/traditional knowledge” are vital contributions to safeguarding socio-economic stability and securing sustainable resource uses in times of stress. The empirical focus is on Central Vietnam, but the argument is relevant in a broader context. The article specifically questions approaches to disaster risk reduction and climate change adaptation that see “local community knowledge” as a vital means to achieving resilience in socio-ecological… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Central government policy is in principle opening up to the effect that rice production strategies vary between provinces (Casse & Milhøj, 2015), yet there is still a dominant focus on rice despite many international concerns of low added value and little technological and institutional innovation (e.g., WB, 2017, p. 2). Fieldwork in the northcentral provinces of Ha Tinh and Nghe An showed that paddy is still mandatory for smallholder farmers in coastal areas with adequate soil and water conditions (Bruun & Olwig, 2015). This is a key area for hybrid rice farming, promoted by state and state-owned enterprise (SOE) corporate interests and linked to Vietnam's massive rice exports.…”
Section: Rural Production and Environmental Governancementioning
confidence: 99%
See 3 more Smart Citations
“…Central government policy is in principle opening up to the effect that rice production strategies vary between provinces (Casse & Milhøj, 2015), yet there is still a dominant focus on rice despite many international concerns of low added value and little technological and institutional innovation (e.g., WB, 2017, p. 2). Fieldwork in the northcentral provinces of Ha Tinh and Nghe An showed that paddy is still mandatory for smallholder farmers in coastal areas with adequate soil and water conditions (Bruun & Olwig, 2015). This is a key area for hybrid rice farming, promoted by state and state-owned enterprise (SOE) corporate interests and linked to Vietnam's massive rice exports.…”
Section: Rural Production and Environmental Governancementioning
confidence: 99%
“…State ownership and a lack of long-term land tenure security severs villagers' attachment to the land and, combined with limited scope for higher value production, add to the unattractiveness of farming. On the part of farmers, there is at the same time a strikingly antirural ideology at play (e.g., Bruun & Olwig, 2015). Apart from a few remaining lineage-based villages, which may trace their history back 400 years, there is little rural romanticism or striving for living close to nature, and few strains of alternative values: Rural villages represent a rather narrow repertoire of life orientations.…”
Section: Rural Production and Environmental Governancementioning
confidence: 99%
See 2 more Smart Citations
“…Communities are being recognized as a major source of adaptation. Thus, there is a need to incorporate indigenous, local, and traditional knowledge systems and practices into adaptation planning to holistically adjust to the effects of climate change [12]. Community-based adaptation programs strengthen social resilience within communities, better integrate efforts to reduce risk against extreme weather events, and make climate change adaptation possible [13].…”
Section: Introductionmentioning
confidence: 99%